Discovering chi tai chi energy exercises for beginner and intermediate - Gazecki, William (Australia: Triple Triangle Company, 1997)
In this DVD, Tai Chi and Chi Gong instructor Linda Modaro intoduces techniques of the ancient masters to improve flexibility, balance and concentration
Title from container
DVD format
Keywords: Qi gong; Exercise; Medicine, Chinese